2003
DOI: 10.1109/tmag.2003.808928
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of positioning error caused by air-flow-induced vibration of head gimbals assembly in hard disk drive

Abstract: Unsteady airflow in an actual hard disk drive (HDD) which has a rotary actuator is numerically simulated by using the large eddy simulation technique, and the aerodynamic force affecting head gimbal assembly (HGA) is estimated from the simulation. The calculated force is fed to a structure analysis to predict the airflow-induced vibration of the HGA. The authors calculate the head positioning error or the head displacements for the different HGA orientations to explain and classify the mechanism of airflow-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…The rapid airflow in the interior of a HDD is highly unsteady with partly laminar and partly turbulent regions, and consists of three regions: 'a solid body inner region near the hub, an outer region dominated by counter rotating vortices and a boundary layer region near the shroud' [6,7]. The turbulent airflow generates unsteady pressure fluctuations or aerodynamic force known as 'windage', causing structural vibration of the HDD components [8].…”
Section: Past Work On Hdd's a Flow-induced Vibration (Fiv)mentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid airflow in the interior of a HDD is highly unsteady with partly laminar and partly turbulent regions, and consists of three regions: 'a solid body inner region near the hub, an outer region dominated by counter rotating vortices and a boundary layer region near the shroud' [6,7]. The turbulent airflow generates unsteady pressure fluctuations or aerodynamic force known as 'windage', causing structural vibration of the HDD components [8].…”
Section: Past Work On Hdd's a Flow-induced Vibration (Fiv)mentioning
confidence: 99%
“…Shimizu et al [8] revealed that pressure fluctuations were generated by vortex shedding from the suspensions and the E-block (HDD arm). Another study also showed that airflow directed towards the outer circumference of the disks collides with the arm, creating a wake region.…”
Section: Past Work On Hdd's a Flow-induced Vibration (Fiv)mentioning
confidence: 99%
“…Many researchers have investigated airflow and flow induced disk flutter and head gimbal assembly vibration by numerical simulation or experimental measurement as reported by Humphrey et al (2002), Shimizu et al (2003), Tsuda et al (2003), Nakamura et al (2005), Aruga et al (2007), and Zhang et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive effort has been made in the past decades in modeling and simulation (M&S) of HDDs for dynamics and vibration analysis of various disk-spindle systems and voice coil motor (VCM)-actuator assemblies, fluid dynamics analysis of disk flutter, and aerodynamic vibration analysis of arm/suspensions (Shen et al 2004;Gao et al 2005a;Tatewaki et al 2001;Shimizu et al 2003). These M&S studies, however, have been carried out from the perspective of enhancing the data read/write precision.…”
Section: Introductionmentioning
confidence: 99%